STRENGTHENING THE LINK BETWEEN GOVERNMENT AND NON-GOVERNMENT ORGANIZATIONS IN TUBERCULOSIS CONTROL IN THE URBAN POOR OF METRO MANILA, PHILIPPINES : A RETROSPECTIVE DESCRIPTIVE STUDY - Aurora G.QUERRI; Akihiro OHKADO; Shoji YOSHIMATSU; Akira SHIMOUCHI (Kekkaku, 2018)
[Abstract] [Objective] To assess the effects of engagement by GOs and NGOs in enhancing access to DOTS facilities and in increasing case finding of TB in the urban poor areas in the Philippines. [Methods] A retrospective descriptive study was conducted to analyze pre- and post-intervention data on DOTS access in two urban poor communities. Data from 2007 to 2012 were collected from participating GOs and NGO DOTS facilities and NGO referring facilities using the National TB Control Program (NTP) monitoring tool. [Results] Attendance rate of presumptive TB in total increased from 1.0% to 1.3% (p<0.01) . Likewise, the notification rate of new smear positive PTB increased from 152 to 167/100,000 (p<0.01). Also, the notification rate of new smear negative /clinically diagnosed PTB increased from 103 to 316/100,000 (p<0.01) . The percent contribution of NGO DOTS facilities in the number of presumptive TB significantly increased from 25% to 30% (p<0.001) . It slightly decreased from 28% to 27% in new smear positive PTB (p=0.737) and it declined from 46% to 35% in new smear negative/clinically diagnosed PTB (p<0.001) . CHVs notified 3% of the total TB cases. Treatment success rate of new smear positive PTB ranged from 82% to 92%. [Discussion] It is clear that the increase in the notification rate of new smear positive PTB with maintained high success rate is satisfactory result of the project obtained by enhanced collaboration of NGOs with GOs. However, considering high BCG vaccination coverage and presence of commonly observed symptoms and without chest x-ray examination, over-diagnosis of pediatric PTB remained highly possible in contact investigation. [Conclusion] The increase in the number of people with TB symptoms examined and TB notifications showed that GO-NGO intervention model was able to improve access to TB services in the urban poor areas in the Philippines. Thus, the engagement of NGOs has complemented the work of GOs in TB control activities to reach more people in the urban community.